Mark Bates on go core techniques and tools : best practices, libraries, and frameworks - Bates, Mark, 1976- (O'Reilly Media, 2015)
"Take the Go programming language out for a test drive with this example-driven video course from software architect Mark Bates. You get a detailed introduction to several tools and techniques that lie at the core of this relatively new Google language, including concurrent programming with "go" routines. Mark also demonstrates how to build a command line application, using test-driven development. Statically typed with syntax derived from C, this easy-to-learn language includes garbage collection, type safety, and some dynamic-typing capabilities. If you're an experienced programmer, you'll have an exciting new language in your toolkit once you complete this video."--Resource description page.